Mathematics communication as an alternative to overcome the obstacles of undergraduate students in mathematical proof - Dewi Risalah; H Hodiyanto (International Journal of Trends in Mathematics Education Research, 2022)
Experiences at the educational personnel education institution, Department of Mathematics Education Institute of Teacher Training and Education Pontianak (IKIP) shows that students often had difficulty in proving propositions (theorems in mathe-matics). The alternative offered through this study was to develop students' abilities in proof through mathematical communication. The study method used in this study was qualitive research, case study. The subjects used in this study consisted of two un-dergraduate students who had been taught real analysis introductions and. The data collection tool used was tests and interview. Data analysis techniques used was de-scriptions: data reduction, data display and conclusion. Based on the results of re-search, study of theory and discussion, it could be concluded in this study that the student obstacles in answering mathematical proof questions are the students have difficulty in writing mathematical symbolic and inability in mathematical proof. But after being given didactic anticipation by mathematical communication, the ability of students to answer mathematical proof questions has increased. Thus, mathematical communication can be used as an alternative to overcome obstacles or difficulties for students in solving mathematical proof problems.